Does Title Increase Large Farm Productivity? Institutional Determinants of Large Land-Based Investments' Performance in Zambia - Ali, Daniel Ayalew (The World Bank, 2021)
Despite accounts of increasing large farm penetration in Africa and an active debate on the differential potential of smallholder versus large farms to satisfy Africa's food requirements, evidence on the extent and performance of different farm types remains limited. A census and subsequent representative survey of 3,000 large farms in Zambia, one of the African countries with the highest share of large farms, allows characterizing the impact of institutional arrangements on large farms' establishment and productive performance. While policies rather than exogenous price shocks seem to have driven large farm expansion, average productivity is not different from small farms and title has no impact on productivity, investment, or credit access, most likely because the transferability of titles remains limited, undermining the suitability of such land as collateral. Significant effects of title on self-reported land prices point toward land being acquired for speculative purposes, suggesting that a tax on titled land, together with improved land service delivery might be a desirable policy option